Vegetable Crops Health Benefits and Cultivation - Yildirim, Ertan; Ekinci, Melek (IntechOpen, 2022)
In ancient times, people benefited from ingesting different parts of various weeds (root, stem, shoot, leaf, flower, fruit, seed, etc.) to maintain a healthy life. People have obtained the vegetables we grow today by succeeding in cultivating these weeds. This book explains the health benefits of vegetable crops, organic vegetable growing, greenhouse management, and principles of irrigation management for vegetable crops.